A genome‐scale yeast library with inducible expression of individual genes - Yuko Arita; Griffin Kim; Zhijian Li; Helena Friesen; Gina Turco; Rebecca Y Wang; Dale Climie; Matej Usaj; Manuel Hotz; Emily H Stoops; Anastasia Baryshnikova; Charles Boone; et al. (Molecular Systems Biology)
Abstract The ability to switch a gene from off to on and monitor dynamic changes provides a powerful approach for probing gene function and elucidating causal regulatory relationships. Here, we developed and characterized YETI (Yeast Estradiol strains with Titratable Induction), a collection in which > 5,600 yeast genes are engineered for transcriptional inducibility with single‐gene precision at their native loci and without plasmids. Each strain contains SGA screening markers and a unique barcode, enabling high‐throughput genetics. We characterized YETI using growth phenotyping and BAR‐seq screens, and we used a YETI allele to identify the regulon of Rof1, showing that it acts to repress transcription. We observed that strains with inducible essential genes that have low native expression can often grow without inducer. Analysis of data from eukaryotic and prokaryotic systems shows that native expression is a variable that can bias promoter‐perturbing screens, including CRISPRi. We engineered a second expression system, Z3EB42, that gives lower expression than Z3EV, a feature enabling conditional activation and repression of lowly expressed essential genes that grow without inducer in the YETI library.